RTL implementation of one-sided jacobi algorithm for singular value decomposition - Wan Mohamad, Wan Ahmad Zainie (2016)
Multi-dimensional digital signal processing such as image processing and image reconstruction involve manipulating of matrix data. Better quality images involve large amount of data, which result in unacceptably slow computation. A parallel processing scheme is a possible solution to solve this problem. This project presented an analysis and comparison to various algorithms for widely used matrix decomposition techniques and various computer architectures. As the result, a parallel implementation of one-sided Jacobi algorithm for computing singular value decomposition (SVD) of a 2х2 matrix on field programmable gate arrays (FPGA) is developed. The proposed SVD design is based on pipelined-datapath architecture The design process is started by evaluating the algorithm using Matlab, design datapath unit and control unit, coding in SystemVerilog HDL, verification and synthesis using Quartus II and simulated on ModelSim-Altera. The original matrix size of 4x4 and 8x8 is used to with the SVD processing element (PE). The result are compared with the Matlab version of the algorithm to evaluate the PE. The computation of SVD can be speed-up of more than 2 by increasing the number of PE at the cost of increased in circuit area.